Honne dan Tatemae dalam Karakter Film Koe no Katachi Karya Yoshitoki Ōima serta Penerapannya dalam Kehidupan Masyarakat Jepang - Mustafa, Reza; Furisari, Pipiet (KIRYOKU, 2025)
The purpose of this study is to analyze the representation of honne (true feelings) and tatemae (social expressions) in the anime film Koe no Katachi by Yoshitoki Ōima, highlighting the dynamics of interpersonal communication in the context of bullying, trauma, and reconciliation. This research employs a descriptive qualitative method using Stuart Hall’s theory of representation and the concepts of honne and tatemae as the analytical framework. Data were drawn from five key dialogue excerpts, analyzed to reveal how verbal and non-verbal expressions represent the dynamics of sincerity and pretense in character interactions. The findings identify three main categories: hidden honne, pleasant tatemae, and strategic tatemae. This study emphasizes the importance of authentic communication in maintaining social harmony and strengthening interpersonal relationships, and its implications are relevant for understanding cross-cultural communication dynamics and their application in character education, particularly in conflict resolution and bullying prevention.